The Groucho/TLE/Grg family of transcriptional co-repressors. - Jennings, B.H.; Ish-Horowicz, D. (Genome Biology, 2008)
The Drosophila Groucho (Gro) protein was the founding member of the family of transcriptional co-repressor proteins that now includes the transducin-like enhancer of split (TLE) and Grorelated gene (Grg) proteins in vertebrates. Gro family proteins do not bind DNA directly, but are recruited by a diverse profile of transcription factors, including members of the Hes, Runx, Nkx, LEF1/Tcf, Pax, Six and c-Myc families. The primary structure of Gro proteins includes five identifiable regions, of which the most highly conserved are the amino-terminal glutamine-rich Q domain and the carboxy-terminal WD-repeat domain. The Q domain contains two coiled-coil motifs that facilitate oligomerization into tetramers and binding to some transcription factors. The WD domain folds to form a beta-propeller, which mediates protein-protein interactions. Many transcription factors interact with the WD domain via a short peptide motif that falls into either of two classes: WRPW and related tetrapeptides; and the 'eh1' motif (FxIxxIL). Gro family proteins are broadly expressed during development and in the adult. They have essential functions in many developmental pathways (including Notch and Wnt signaling) and are implicated in the pathogenesis of some cancers. The molecular mechanisms through which Gro proteins act to repress transcription are not yet well understood. It is becoming clear that Gro proteins have different modes of action in vivo dependent on biological context and these include direct and indirect modification of chromatin structure at target genes.